If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 42x + -18y + 35x + 47y = 0 Reorder the terms: 42x + 35x + -18y + 47y = 0 Combine like terms: 42x + 35x = 77x 77x + -18y + 47y = 0 Combine like terms: -18y + 47y = 29y 77x + 29y = 0 Solving 77x + 29y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-29y' to each side of the equation. 77x + 29y + -29y = 0 + -29y Combine like terms: 29y + -29y = 0 77x + 0 = 0 + -29y 77x = 0 + -29y Remove the zero: 77x = -29y Divide each side by '77'. x = -0.3766233766y Simplifying x = -0.3766233766y
| 7(-2a)=5(-3a+1) | | .4c-125=375 | | -x^2+5x=-y | | 10=-6x+16 | | 72=4x+2 | | 2x+40+x=180 | | 6(y+2)-4=6y | | 6(n-1)+4n=-86 | | 5x+12=-3x-28 | | .82=logx | | 3(3+3x)=8(x-5) | | 2.8y-7=12.85y-2 | | 2.8-7=12.85y-2 | | 59-3u=75 | | 4x+2=72 | | -5[x+3]+3=-17 | | -14v+14v=-10v | | 2y+5x-z=4y+6x | | 9x-2=9(x-7) | | 2(m-8)+7=5(m+2)-3m-19 | | 3.4=-13.6+(3.4c)+1.7 | | -[2x-8]-6=-12 | | F(-x)=3x^2+6x-5 | | x+4+2x=6x-8 | | 4(3x+4)-20=3+5x | | 4x+26=-38 | | 6w-15=9w+8 | | 11x-11=2x+16 | | 4=3(m+4) | | 4(6+x)-5=x-3 | | 25(x-3)=12(x+2)-10 | | -6=x-13 |